Chemical profiling of Ulva species for food applications: What is in a name?. (1st November 2021) - Roleda, Michael Y.; Heesch, Svenja
Abstract: Seaweeds are increasingly used in European cuisine. Until the recent use of molecular techniques, species identification was solely based on morphology which cannot easily discriminate morphologically simple but phenotypically plastic taxa such as the green algal genus Ulva . For example, current taxonomic protocol effectively reassigned the previously known European ʻUlva lactuca L.' under the name Ulva fenestrata Postels & Ruprecht. Also, the presumptive Ulva lactuca approved by the Institute for Reference Materials and Measurements (IRMM, Joint Research Center, European Commission) as Certified Reference Material (CRM) for analytical quality assurance was genetically identified as U . rigida C.Agardh. It is very likely that different Ulva species under various names have been consumed as food not only in Europe, but also worldwide. In this regard, when chemical composition and nutritional quality of different seaweed species meet a set of food standard criteria, and food safety hazards are mitigated, they should be endorsed for consumption. In the case of Ulva, we propose that different bladed and tubular species should generally be accepted for food consumption in Europe.